Analisis Kontribusi Model Pembelajaran EMKONTAN terhadap Kreativitas dan Literasi Lingkungan dalam Memecahkan Masalah Lingkungan pada Siswa SMA Muhammadiyah 3 Batu - Yuniarti, Fenti Nur; Nurwidodo, Nurwidodo; Hadi, Samsun (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Education is crucial to shape the quality of superior and competitive human resources. challenges to the quality of education in Indonesia, especially related to the low creativity and environmental literacy of high school students, as well as the lack of participation in real environmental issues. The EMKONTAN learning model is proposed as an innovation to overcome these problems, because it integrates local environmental issues and encourages experience-based problem solving. This study investigates the impact of the EMKONTAN model on enhancing creativity and environmental literacy in solving ecological issues among 19 tenth-grade students at SMA Muhammadiyah 3 Batu, using a one-group pretest-posttest quasi-experimental design. Data were collected through creativity and environmental literacy tests, and observation. The data analysis with paired sample t-test showed a significant increase in both variables. The average creativity score increased from 36.00 (pre-test) to 39.42 (post-test), with a p value <0.001. Environmental literacy also increased significantly from 180.89 (pre-test) to 195.37 (post-test), with a p value <0.001. These findings indicate that the EMKONTAN learning model is effective in improving students' creative thinking skills and environmental literacy in solving environmental problems. This model encourages students to think critically, innovate, and understand environmental issues deeply through direct experience and reflection.